PROFESSIONAL PREPARATION OF TEACHERS TO DEVELOP PUPILS' SPATIAL THINKING - Alevtina V. Vasilenko (Moscow Polytechnic University, 2016)
This article presents the structure of professional training of future teachers to develop pupils' spatial thinking. The authors dwells on some features of the organization of students' psychological training on the basic, higher and creative levels with the use of interactive forms of the activities.